Case report: Resolution of malignant canine mast cell tumor using ketogenic metabolic therapy alone - Seyfried, Thomas N.; Mukherjee, Purna; Lee, Derek C.; Ta, Linh; Nations, Loren (Frontiers in Nutrition, 2023)
Background Mast cell tumours (MCT) are common malignant neoplasms in dogs and are similar to most other malignant cancers in requiring glucose for growth, regardless of histological grade. Ketogenic metabolic therapy (KMT) is emerging as a non-toxic nutritional intervention for cancer management in animals and humans. We report the case of a 7-year-old Pit Bull terrier that presented in 2011 with a cutaneous mast cell tumour under the right nostril. Methods The patient’s parent refused standard of care (SOC) and steroid medication after initial tumour diagnosis due to the unacceptable adverse effects of these treatments. Following tumour diagnosis, the patient’s diet was switched from Ol’Roy dog food to raw vegetables. The tumour continued to grow on this diet until July, 2013 when the diet was switched to a natural calorie restricted ketogenic. A dog food calculator was used to reduce calories to 60% (40% calorie restriction) of that consumed on the original diet. A total of 444 kilocalories were given twice/day at 12 hr. intervals with one medium-sized raw radish given as a treat between each meal. Results The tumour grew to about 3-4 centimeters and spread to surrounding tissues while the patient was on the raw vegetable diet. The tumour gradually disappeared over a period of several months when the patient was switched to the natural calorie restricted ketogenic diet. The patient lost 2.5 kg during the course of the calorie restriction and maintained an attentive and active behavior. The patient passed away without pain on June 4, 2019 (age 15 years) from failure to thrive due to an enlarged heart with no evidence of mast cell tumour recurrence. Conclusion This is the first report of a malignant cutaneous mast cell tumour in a dog treated with KMT alone. The resolution of the tumour in this canine patient could have been due to the diet-induced energy stress and the restriction of glucose-driven aerobic fermentation that is essential for the growth of most malignant tumours. Further studies are needed to determine if this non-toxic dietary therapeutic strategy could be effective in managing other canine patients with malignant mast cell tumours.